2015
DOI: 10.1002/fsn3.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methyl cellulose coating on physicochemical properties, porosity, and surface diameter of pistachio hull

Abstract: Pistachio is a nut with high consumption that can be affected by aflatoxin contamination. Regarding influence of this fungus on global trade, broad studies in this area seem to be necessary. In this research, pistachio nuts were coated with methyl cellulose at different concentrations of 0.1%, 0.5%, 1%, and 2% by immersion method. Samples were stored in an incubator (25°C) for 4 months. Imaging was performed by electron microscope using SEM method and chemical changes (moisture, iodine, peroxide, and acidic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Peroxide formation proceeds slowly in the initial stages of oxidation. However, in the later stages, it acts as a catalyst in oil oxidation (Moslehi et al, 2015). In this study, the PV increased for all walnut samples during the storage period.…”
Section: Chemical Analysis: Peroxide Value Conjugated Dienes and Trisupporting
confidence: 46%
See 2 more Smart Citations
“…Peroxide formation proceeds slowly in the initial stages of oxidation. However, in the later stages, it acts as a catalyst in oil oxidation (Moslehi et al, 2015). In this study, the PV increased for all walnut samples during the storage period.…”
Section: Chemical Analysis: Peroxide Value Conjugated Dienes and Trisupporting
confidence: 46%
“…Once more, MC acted as a barrier between walnuts and the atmosphere, preventing gas exchange and, as a consequence, lipid oxidation. This was previously studied in coated pistachios (Moslehi et al, 2015) and avocados (Maftoonazad and Ramaswamy, 2005) where MC coating lessened moisture losses and respiration rates. Other studies have also found lower values of CD in products protected with edible coatings.…”
Section: Chemical Analysis: Peroxide Value Conjugated Dienes and Trimentioning
confidence: 99%
See 1 more Smart Citation
“…Extract, on the one hand, had an effect on reducing the moisture absorption of coating and, on the other hand, increased the shelf life of the nuts by decreasing the permeability of the coating to oxygen (Haq et al., 2013). These results were in agreement with others (Hashemi et al, 2020; Moslehi et al, 2015; Sabaghi et al., 2015), confirmed that a higher concentration of coating materials, extract, or essential oil decreases the peroxide value of nuts.…”
Section: Resultssupporting
confidence: 93%
“…However the rate of increase in diene content in later stages of heating is expected to be lower, finally reaching a plateau due to the establishment of equilibrium between the rates of formation of conjugated dienes to that of polymers [36]. Peroxide value (PV) is also used to determine the rate of lipid peroxidation especially during the initial stage [37]. Lipid hydroperoxide is one parameter that is commonly measured in lipids to determine their oxidation state; however, iodometric titration is one preferred method for the determination of lipid hydroperoxide level as peroxide value (PV).…”
Section: Propagation Stage Of Lipid Peroxidationmentioning
confidence: 99%